2000
DOI: 10.1073/pnas.140063197
|View full text |Cite
|
Sign up to set email alerts
|

In organello formaldehyde crosslinking of proteins to mtDNA: Identification of bifunctional proteins

Abstract: The segregating unit of mtDNA is a protein-DNA complex called the nucleoid. In an effort to understand how nucleoid proteins contribute to mtDNA organization and inheritance, we have developed an in organello formaldehyde crosslinking procedure to identify proteins associated with mtDNA. Using highly purified mitochondria, we observed a time-dependent crosslinking of protein to mtDNA as determined by sedimentation through isopycnic cesium chloride gradients. We detected Ϸ20 proteins crosslinked to mtDNA and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
140
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 41 publications
11
140
0
Order By: Relevance
“…Enzymes such as aconitase, isocitrate dehydrogenase and Kgd2p (a subunit of KGDHC in yeast equivalent to E2k in mammal), are found to have two or more different functions (51)(52)(53)(54)(55)(56). For example, Kgd2p in yeast participates in both the tricarboxylic acid cycle and ϩ mtDNA maintenance (56).…”
Section: E2k Depletion and Cell Functionmentioning
confidence: 99%
“…Enzymes such as aconitase, isocitrate dehydrogenase and Kgd2p (a subunit of KGDHC in yeast equivalent to E2k in mammal), are found to have two or more different functions (51)(52)(53)(54)(55)(56). For example, Kgd2p in yeast participates in both the tricarboxylic acid cycle and ϩ mtDNA maintenance (56).…”
Section: E2k Depletion and Cell Functionmentioning
confidence: 99%
“…In several cases it has been observed that the form of mitochondrial genome may differ among closely related species (Bridge et al, 1992;Fukuhara et al, 1993;Martin, 1995;Laflamme & Lee, 2003). Investigations of mtDNA-binding proteins indicate that similar machineries are responsible for the maintenance of both forms (Miyakawa et al, 1995(Miyakawa et al, , 1996Nosek et al, 1999;Kaufman et al, 2000;Tomaska et al, 2001). The occurrence of linearand circular-mapping genomes in different strains of the same species indicates that both types of mitochondrial genome do not differ radically in their life styles (Fukuhara et al, 1993).…”
Section: Evolutionary Implicationsmentioning
confidence: 99%
“…B, mitochondria and cytosolic post-mitochondrial fractions were prepared from HTC-IR cells grown in serum as outlined in A. Organelle markers were used to verify the mitochondria isolation procedure. Equal amounts of protein from the cytosolic post-mitochondrial fraction (Supernatant II) and from the purified mitochondria were resolved by SDS-PAGE and after electrotransfer the PVDF membrane was stained with antibody to the mitochondrial proteins, HSP60 (71), and cytochrome c (39), and to the endoplasmic protein GRP 94 (42). C, total RNA purified from mitochondrial and from cytosolic post-mitochondrial fractions was used in RT.…”
Section: K Protein Binds To Sequences Within the 3ј-utr Of The Ratmentioning
confidence: 99%